Visualization and quantification of local concentration gradients in evaporating water/glycerol droplets with micrometer resolution - Alexander Erb; Jonas Kind; Timon L. Zankel; Robert W. Stark; Christina M. Thiele (Proceedings of the National Academy of Sciences, 2025)
Evaporation of sessile multicomponent droplets is ubiquitous in many common processes, such as printing, cooling, and coating. The evaporation rate is not evenly distributed across the surface of the droplet. As a result, there are regions with high evaporation rates in which the more volatile part evaporates preferentially; this can induce local surface tension gradients, which, in combination with density differences, can lead to flows within the droplet originating from local concentration gradients. Current experimental methods are based on the addition of markers that can alter liquid properties. Thus, marker-free experimental evidence for the concentration fields proposed is needed. In this work, we use Raman imaging and MRI to quantify concentration gradients in 4.2 μL droplets of 90 mol% water and 10 mol% glycerol. MRI concentration maps with 33 μm resolution enable the investigation of local concentrations as close as 100 μm to the 3-phase contact line. Raman imaging allows even higher resolution and longer observation times. The results of both methods are in excellent agreement. In accordance with the simulations, an increasing glycerol content close to the 3-phase contact line was found. Close to the droplet apex, the glycerol content decreased. The horizontal and vertical concentration gradients were on the order of 1 × 10 −2 mol%μm −1 . These findings can be used for the development and optimization of inks, medical diagnostic devices, food processing procedures, 3D bioprinting, and many more; they might provide the experimental concentration fields sought for the optimization of simulations.